Social Media Utilization and Academic Performance of Students Studying Geography in Public Secondary Schools in Nsit Atai Local Government Area, Akwa Ibom State, Nigeria - Nsidibe Mbuotidem Sampson; Mbuotidem Sampson Ebong (Faculty of Teacher Training and Education, Universitas Terbuka, 2019)
This project was an investigation on the utilization of social media and academic performance of students in Geography in Nsit Atai Local Government Area of Akwa Ibom State, Nigeria. Four schools out of six public secondary schools in Nsit Atai Local Government Area were selected for the study. The population size was 1108 students, while the sample size was 100 students. The correlational research design was adopted for the study. The instruments for data collection were Social Media Utilization Questionnaire (SMUQ) and Geography Achievement Test (GAT). The instruments were validated by the supervisor and tested for reliability; a reliability coefficient of 0.78 was obtained using the test-retest method reliability test. Two research questions and null hypotheses, respectively were stated to guide the study. Data obtained from the students using the SMUQ and GAT were analyzed using the Pearson Product Moment Correlation Coefficient (PPMC).The hypotheses were tested at .05 alpha level of significance. Concerning the findings of this study, it was deduced that there was a fragile positive relationship between studentsÃ¢â‚¬â„¢ utilization of Whastapp, as well as Facebook social media and their academic performance in Geography. Based on the findings, it was recommended among others that social media utilization should be encouraged among students as this will help them develop excellent communication skills, build interactions, share ideas and enhance collaboration between students, teachers, and parents alike.Ã‚Â